Perceptual Simulations and Linguistic Representations Have Differential Effects on Speeded Relatedness Judgments and Recognition Memory - Tse, Chi-Shing (2009)
We examined the effect of spatial iconicity (a perceptual simulation of canonical locations of objects) and word-order frequency on language processing and episodic memory of orientation. Participants made speeded relatedness judgments to pairs of words presented in locations typical to their real world arrangements (e.g., ceiling on top and floor on bottom). They then engaged in a surprise orientation recognition task for the word pairs. We replicated Louwerse’s finding (2008) that word-order frequency has a stronger effect on semantic relatedness judgments than spatial iconicity. This is consistent with recent suggestions that linguistic representations have a stronger impact on immediate decisions about verbal materials than perceptual simulations. In contrast, spatial iconicity enhanced episodic memory of orientation to a greater extent than word-order frequency did. This new finding indicates that perceptual simulations have an important role in episodic memory. Results are discussed with respect to theories of perceptual representation and linguistic processing.